If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4(3+f)6f=-24
We move all terms to the left:
-4(3+f)6f-(-24)=0
We add all the numbers together, and all the variables
-4(f+3)6f-(-24)=0
We add all the numbers together, and all the variables
-4(f+3)6f+24=0
We multiply parentheses
-24f^2-72f+24=0
a = -24; b = -72; c = +24;
Δ = b2-4ac
Δ = -722-4·(-24)·24
Δ = 7488
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$f_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$f_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{7488}=\sqrt{576*13}=\sqrt{576}*\sqrt{13}=24\sqrt{13}$$f_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-72)-24\sqrt{13}}{2*-24}=\frac{72-24\sqrt{13}}{-48} $$f_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-72)+24\sqrt{13}}{2*-24}=\frac{72+24\sqrt{13}}{-48} $
| 2z+23=2z+60 | | 110+14z=180 | | 9y+7+2y+98=180 | | 14z+9(12)+2=180 | | 8w=16÷3 | | 70+12y+2=180 | | 6b+b=7b | | x^2-9x+2)=0 | | x(x^2-9x+20)=0 | | 60+12y+2=180 | | h()=2h(3) | | 28000+3000x=36000+2000x=18000+x | | -5z-34=14-z | | f-32=1.80C | | x+18=43+3x | | (2x-10)(×+6)=0 | | x-8+5=20 | | x-8+9=20 | | 6x^2+82x-5500=0 | | 1.4−x=−1.9 | | 7+2x+4=5x-6-2x+5 | | 2/7=4/y | | 3x-50=58 | | 60=-c | | 3x-2(4x-10)=5x | | 6.8=3.5-x | | 1120=28(p+10) | | 0.5f−0.7=0.3 | | H=-2t+38 | | 5x+3-7=13 | | -2=2k-8 | | 3(-5+x)+10=40 |